SISTEM IJON PADA USAHATANI CENGKEH DI DESA RAANAN BARU KECAMATAN MOTOLING BARAT KABUPATEN MINAHASA SELATAN - Sandro ., Pangemanan; Rine ., Kaunang; Jean F. J. Timban (Sam Ratulangi University, 2018)
This study aims to describe the prevailing sijon system in clove farming in Raanan Baru Village, West Motoling Subdistrict. This research was conducted for 3 (three) months starting from the preparation phase until the preparation of the report that is since December 2017 s / d February 2018. The data used in this study is primary data which is research data obtained directly from the farmers as respondents and data secondary data which is a research data obtained indirectly through agency information or documents relating to this research and village data. Sampling method in this study using purposive sampling method, meaning that researchers determine their own samples taken because there are certain considerations. Data Analysis Method in this research is processed by using descriptive analysis and then Analysis This data is processed / presented in written form and table. The process of bond transfers in Raanan Baru Village has been going on for generations and has even taken root in the village community itself. From the results of case studies encountered in the field stated that the transaction system of ijon that occurred in Raanan Baru Village, West Motoling Subdistrict of South Minahasa Regency is done on the basis of both parties have agreed and have good intention to do the transaction of debt by only having mutual trust with each other.